The gap between rhetorical education and civic discourse. Issue 2 (2nd July 2016) - Rood, Craig
ABSTRACT: I urge more communication rhetoricians to devote scholarly attention to rhetorical education. Toward that end, this essay examines the gap between rhetorical education and civic discourse. Pedagogical initiatives, while essential, must be complemented by scholarly work that conceptualizes, assesses, and contextualizes this gap.